Moderating effect of volatile environment on the relationship between entrepreneurial orientation, market orientation, change implementation capacity and SMEs performance of retail firms - Mohd Nizam, Abdul Kadir (2019)
Retail business plays a vital role in many economies by providing employment opportunity, generating the gross national income progressively, and contributing to the growth of SMEs. However, the determining factors of the performance of SMEs have not been extensively explored. Thus, the main objective of this study is to examine three determinants, namely, market orientation (MO), entrepreneurial orientation (EO) and change implementation capacity (CIC) and their effects towards the SMEs performance (FP) for the retail subsector. This study also incorporates the moderating effect of volatile environment (VE) in examining its influence between the determinants and FP. Data were collected from the owner-managers of SME-sized retail firms that were located within the central region of Peninsular Malaysia using the crosssectional study design. This study adopted stratified sampling and 373 SMEs retail firms had been randomly selected. Survey method had been used in which 152 acceptable returned responses were analysed using the PLS-SEM regression statistical technique. Results indicated that MO and CIC had significant positive effects on FP. EO, on the other hand, did not have any positive effect on FP. The findings also revealed that VE had a moderating effect on MOFP and CIC-FP, but not for EO-FP. Theoretical contribution that had been made by this study was by integrating the variables from the theory of Dynamic Capabilities View with construct from the Resource-based View theory, in which the results have extended the body of knowledge in SMEs literature. The findings of this study also provide important insights to the owner-managers, researchers and policy-makers to further understand the determinants of SMEs performance of retail firms and the effects of environment volatility surrounding the business. Finally, limitations of current study and avenues for future research are also discussed.